Navigating Financial Distress: Altman Z-Score Predictive Power on Stock Performance - Sari, Dewi Maya; Mislinawati, Mislinawati (Jurnal Sains Riset, 2024)
The study aims to analyze the effect of the financial ratio component in the Altman Z-Score model on the stock price. The data used is the financial report data of the agro- and marine-industry companies listed on the Indonesian Stock Exchange from 2018 until 2020. The data is analyzed using panel data analysis methods. The calculation of the Z-Score value shows how many companies in the agro- and marine sectors are potentially bankrupt. Research results show that the RE/TA ratio has a positive and significant effect on the stock price, while the WC/TA, EBIT/TA, and MVE/BVL ratios have a negative effect on the stock price. The results of this research will imply that financial managers, auditors, lenders, and investors can make the Z-Score model a valuable instrumental indicator in making the right decisions in the face of financial distress.Keywords : Financial distress; Stock Price; Financial Ratio; Altman Z-Score